Prevalence of hearing loss due to ossicular chain involvement in rheumatoid arthritis - S., Ramesh; D., Gurumoorthy A. (International Journal of Research in Medical Sciences, 2018)
Background: Rheumatoid Arthritis (RA) is a chronic multisystem disease commonly affecting the synovial joints. Involvement of middle ear ossicular chain in RA may lead to hearing loss. The effects of hearing loss are profound, with consequences in the social, functional, and psychological well-being of the persons affected. Both conductive and sensorineural types of hearing impairments have been found in these patients in various studies. This study aimed at evaluating the prevalence of hearing impairment in our patients. Methods: Pure tone and impedance audiograms were taken for 100 RA patients who came to the outpatient department. They were divided into three groups based on their disease activity (DAS28). The hearing thresholds were compared among these groups. Tympanographic features and acoustic reflexes were recorded. Disease duration was also taken into account for asessing the severity of hearing impairment. Results: Out of 100 patients, 52 patients had significant hearing impairment audiometrically, of which 44 had sensorineural, 1 conductive and 7 mixed impairments. No significant difference was found between the hearing thresholds and the disease activity but those with high disease activity had higher incidence of abnormal tympanograms (72.2%) and absence of acoustic reflex (55.5%). Prevalence of hearing impairment was found to be increased with increasing disease duration, with steep rise between 5 and 10 years of disease duration. Conclusions: Hearing impairment affects the quality of life adversely. Severity of hearing impairment is significantly associated with having a hearing-related handicap and with self-reported communication difficulties. Thus, hearing assessment if done routinely can improve the outcome in these patients.